1991
DOI: 10.1161/01.str.22.4.489
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase decreases mortality, blood pressure, and cerebral blood flow responses induced by acute hypertension in rats.

Abstract: Oxygen radicals are known to be produced by the cerebral vasculature during acute, pressor-induced hypertension and are also known to inactivate endothelium-derived relaxing factor. The objective of our present study was to determine if the oxygen radical scavenger superoxide dismutase (24,000 units/kg plus 1,600 units/kg/min) alters the pressor, cerebral blood flow, and mortality responses to systemic norepinephrine in rats. Increasing doses (0.01-30 /tg/kg i.v.) of norepinephrine were given by bolus injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
2
22
1
Order By: Relevance
“…12 Thus, it is logical to hypothesize that high intraluminal pressure (P i ) itself can also promote vascular O 2 ·Ϫ generation in hypertension. This idea is congruent with previous observations that even short-term increases in P i , both in vivo and in vitro, impair endothelial function, [13][14][15][16] an effect that can be prevented by superoxide dismutase (SOD). 17 However, the possible role of high P i alone in the upregulation of arterial O 2 ·Ϫ production and the underlying signaling mechanisms has not yet been elucidated.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…12 Thus, it is logical to hypothesize that high intraluminal pressure (P i ) itself can also promote vascular O 2 ·Ϫ generation in hypertension. This idea is congruent with previous observations that even short-term increases in P i , both in vivo and in vitro, impair endothelial function, [13][14][15][16] an effect that can be prevented by superoxide dismutase (SOD). 17 However, the possible role of high P i alone in the upregulation of arterial O 2 ·Ϫ production and the underlying signaling mechanisms has not yet been elucidated.…”
supporting
confidence: 91%
“…17 Other studies also showed that in the coronary and cerebral circulation, short-term increases in P i in vivo also impair endothelial function. [13][14][15][16] Mechanosensitive production of reactive oxygen species has also been linked to pressure-induced constriction of arterioles. 24,25 To provide further evidence for high P iinduced oxidative stress, we demonstrated with real-time lucigenin chemiluminescence measurements that high P i itself induced significant increases in arterial O 2 ·Ϫ generation (Figures 2A and 2B), whereas normal levels of P i had minimal effect.…”
Section: Pressure-induced Increase In Arterial O 2 ·؊ Generationmentioning
confidence: 99%
“…Similar observations have also been reported in ex vivo studies in that treatments of SHR aortic rings with ROS-scavengers such as Tiron or mercaptopropionylglycine (MPG) reverse oxidative stress-mediated endothelial dysfunction and decrease p22-phox expression, O 2 -generation and overall NAD(P)H oxidase activity [40]. CuZn-SOD prevents vascular damage and increases survival in rats made hypertensive by ang II or norepinephrine infusion [208]. Similarly, overexpression of Mn-SOD using gene transfer techniques has been shown to reduce ROS levels and improve endothelial function in a number of disease states associated with endothelial dysfunction such as diabetes and low-renin model of hypertension [209,210].…”
Section: Antioxidant Enzymessupporting
confidence: 74%
“…44 Additional data in other models of hypertension support the notion that oxygenderived free radicals contribute to either the causes or consequences of hypertension. 45 As mentioned above, these 4 risk factors (hypercholesterolemia, diabetes mellitus, hypertension, and smoking) are related to oxidative stress, which plays a major role in atherogenesis. At present, we do not know precisely why the development of CAD is associated with the genotype of (GT) n repeats in the human HO-1 gene promoter only in patients with hypercholesterolemia or diabetes mellitus or in smokers.…”
Section: Kaneda Et Al Heme Oxygenase Gene Promoter Polymorphism and Cadmentioning
confidence: 99%